New approaches: an example from Niger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The IFAD-funded soil and water conservation project in Niger`s Illela District is a model for the restoration of degraded and abandoned land, based on simple and replicable methods which are implemented by the local people. The project started in...